Features of the narrative world of Russian Orthodoxy in late 2015 - early 2016 - Svitlana Shkil (Cхід, 2016)
The article considers the features contemporary transformations narratives official Russian Orthodoxy in the years 2015-2016. At the end of 2015 and in 2016 narrative "Russian world" Patriarch and his entourage tried to upgrade using the ideal of "solidarity." The ideas of "solidarity" in the XX century evolved differently in Catholic social teaching and fascism. Spokesman of the Russian Orthodox Church sees the embodiment of the ideals of solidarity in the best manifestations of Soviet mentality. "Solidarism" in the rhetoric of the Patriarch and his entourage are a means of legitimizing Russian nationalism and revanchism. According to the Patriarch of core values and "Russian world" is "faith, state, justice, solidarity and dignity." These values must be an alternative to liberal values - freedom, rights, human rights. According to Patriarch values should determine the policy, and especially value the unity of the Russian people and state. This means that the patriarch claim to symbolic power over the politicians of Russia and neighboring countries. Іn rhetoric of patriarch the West, with its core value of freedom, embodies evil. Russia tempted by Western values, and this is the cause of many crises. The role of savior in this narrative belongs to the church and its leadership. Present rated as the culmination of the struggle between good and evil. The future victory of good patriarch linked not only to preserve the unity and uniqueness of Russia, but the triumph of traditionalism in Europe, the adoption of the values of solidarity society.